2021
DOI: 10.1128/jvi.02030-20
|View full text |Cite
|
Sign up to set email alerts
|

A Human Endogenous Bornavirus-Like Nucleoprotein Encodes a Mitochondrial Protein Associated with Cell Viability

Abstract: Endogenous retroviruses (ERVs) are sequences in animal genomes that originated from ancient retrovirus infections; they provide genetic novelty in hosts by being co-opted as functional genes or elements during evolution. Recently, we demonstrated that endogenous elements from not only retroviruses but also from non-retroviral RNA viruses are a possible source of functional genes in host animals. The remnants of ancient bornavirus infections, called endogenous bornavirus-like elements (EBLs), are present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Since then, several homologous sequences of BoDV-1 N protein in the human genome and in the genome of a wide array of species were found and were termed as endogenous Bornavirus-like elements (EBLN). The tissue-dependent transcription of some of these genes as well as the translation of at least the ORF-encoding human EBLN hsEBLN-2 into a functional mitochondrial protein with certain functions was demonstrated [ 27 , 28 , 29 ]. In addition, homologous sequences for BoDV-1 M, G, and L protein have been found in the genome (termed EBLM, EBLG and EBLL) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several homologous sequences of BoDV-1 N protein in the human genome and in the genome of a wide array of species were found and were termed as endogenous Bornavirus-like elements (EBLN). The tissue-dependent transcription of some of these genes as well as the translation of at least the ORF-encoding human EBLN hsEBLN-2 into a functional mitochondrial protein with certain functions was demonstrated [ 27 , 28 , 29 ]. In addition, homologous sequences for BoDV-1 M, G, and L protein have been found in the genome (termed EBLM, EBLG and EBLL) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which vertebrate EPVs have reached fixation through positive selection as opposed to incidental factors such as founder effects, population bottlenecks, and genetic hitchhiking remains unclear. Potentially, EPVs might sometimes be co-opted or “exapted” as has been reported for EVEs derived from other virus groups [ 44 46 ]. Recent studies have identified EPVs in the germline of degus ( Octodon degus ) and elephants (family Elephantidae) that encode intact Rep ORFs and exhibit similar patterns of tissue-specific mRNA expression in the liver [ 37 , 38 ], suggesting that expression of Rep protein or mRNA may be physiologically relevant in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…25,35,36 The HAX-1 has been preferentially located in the mitochondria in the cell, and in a small part, on the endoplasmic reticulum and nuclear membrane, which was primarily inferred to be related to cell apoptosis. 37 However, some studies have demonstrated that the effect of HAX-1 on apoptosis was controversial. Human and rat HAX-1 genes have been severely spliced, resulting in at least 7 different variants, mainly due to the differences in the NH2 ends.…”
Section: Discussionmentioning
confidence: 99%
“…43 The important role of HAX-1 in cell protection might also be related to the inhibition of mitochondrial and endoplasmic reticulum apoptosis pathways. 37 The HAX-1 also had certain effects on the nervous system. Studies have shown that HAX-1 had a neuroprotective effect against ischemic neuronal injury, and apoptosis after cerebral ischemia was induced by the downregulation of HAX-1 by NOX2-produced reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%